Auditory Delta Event-related Oscillatory Responses are Decreased in Alzheimer's Disease - Yener, Görsev; Güntekin, Bahar; Necioğlu Örken, Dilek; Forta, H.; BAŞAR, EROL (Ios Press, Nieuwe Hemweg 6B, 1013 Bg Amsterdam, Netherlands, 2012)
Background: Visual delta event-related (ERO) and evoked oscillations (EO) of Alzheimer patients (AD) are different than healthy. In the present study, the analysis is extented to include auditory ERO and EO in AD. The rationale is to reveal whether the auditory ERO delta responses are also reduced, and whether this is a general phenomenon in Alzheimer patients upon applying stimuli with cognitive load. Methods.: Thirty-four mild AD subjects 117 de-novo and 17 medicated (cholinergic)l and seventeen healthy controls were included. Auditory oddball paradigm and sensory auditory stimuli were applied to the subjects. Oscillatory responses were analyzed by measuring maximum amplitudes in delta frequency range (0.5-3.5 Hz). Results: Auditory delta ERO (0.5-3.5 Hz) responses of healthy controls were higher than either de-novo AD or medicated AD group, without a difference between two AD subgroups. Furthermore, the auditory EO after presentation of tone bursts yielded no group difference. Conclusion: Our findings imply that delta ERO is highly unstable in AD patients in comparison to age-matched healthy controls only during the cognitive paradigm. Our results favor the hypothesis that neural delta networks are activated during cognitive tasks and that the reduced delta response is a general phenomenon in AD, due to cognitive impairment.
Keywords: alzheimer; P300; oscillations; auditory; delta; cholinergic; mild cognitive impairment; working-memory task; brain oscillations; theta-oscillations; EEG; alpha; rhythms; electroencephalography; schizophrenia; salınımlar; işitsel; delta; kolinerjik; hafif kognitif bozukluk; çalışma-bellek görev; beyin salınımları; teta-salınımları; alfa; ritimler; elektroensefalografi; şizofreni